Negative Events at Workplace and In Role Performance: Implications of Affective Events Theory (AET) - BANO, AZRA; ASHRAF, SHAGUFTA; KHAN, DR. MUHAMMAD MAROOF; KHAN, DR. MUHAMMAD MUDASSAR; MEHMOOD, SHAHID (The journal of contemporary issues in business and government, 2021)
In health care centers front line nurses are the major people who are responsible for treatment of the patients thus they need highly supportive organization to perform their tasks efficiently and effectively. Workplace bullying has negative outcomes for any type of organization/employee. Thus this needs to be controlled by the management of the concerning organization. Therefore current research is designed to identify the outcomes of workplace bullying for in role performances of specialized nurses in Pakistan. Psychological distress is also great interest of researcher to use it as mediator among workplace bullying and in role performance. By using convenient sampling technique 200 nurses were selected as sample of current study. In current research self-administered questionnaires are used to collect the data. Latest version of SPSS has been deployed for analysis of data. Further MACRO Process by Preacher and Hayes was used to test the mediation of the current research. Findings revealed that workplace bullying has drastic results for in-role performance of the specialized nurses and it is also found that psychological distress mediates the relationship among workplace bullying and in role performance. The respondents who have explicit presentation, who fill in as specific nursing administrations suppliers' the outcome of this investigation attested that there is an association between workplace bullying, job autonomy. Besides, results exhibited that movement freedom can play positive task to redesign on in role performance. It is furthermore investigated that psychological distress as an arbiter in this examination. There is critical negative relationship among workplace bullying and on in role performance. The association between work place bullying, workers’ in job autonomy and furthermore demonstrated that activity independence can play positive job to upgrade on in role performance.